Stoichiometric and Catalytic (η5-Cyclopentadienyl)cobalt-Mediated Cycloisomerizations of Ene-Yne-Ene Type Allyl Propargyl Ethers - Chang, Chu-An; Gürtzgen, Stefan; Johnson, Erik P.; Vollhardt, K. Peter C. (Synthesis, 2020)
The complexes CpCoL2 (Cp = C5H5; L = CO or CH2=CH2) mediate the cycloisomerizations of α,δ,ω-enynenes containing allylic ether linkages to 3-(oxacyclopentyl or cycloalkyl)furans via the intermediacy of isolable CpCo-η4-dienes. A suggested mechanism comprises initial complexation of the triple bond and one of the double bonds, then oxidative coupling to a cobalt-2-cyclopentene, terminal double bond insertion to assemble a cobalta-4-cycloheptene, β-hydride elimination, and reductive elimination to furnish a CpCo-η4-diene. When possible, the cascade continues through cobalt-mediated hydride shifts and dissociation of the aromatic furan ring. The outcome of a deuterium labeling experiment supports this hypothesis. The reaction exhibits variable stereoselectivity with a preference for the trans-product (or, when arrested, its syn-Me CpCo-η4-diene precursor), but is completely regioselective in cases in which the two alkyne substituents are differentiated electronically by the presence or absence of an embedded oxygen. Regioselectivity is also attained by steric discrimination or blocking one of the two possible β-hydride elimination pathways. When furan formation is obviated by such regiocontrol, the sequence terminates in a stable CpCo-η4-diene complex. The conversion of the cyclohexane-fused substrate methylidene-2-[5-(2-propenyloxy)-3-pentynyl]cyclohexane into mainly 1-[(1R*,3aS*,7aS*)-7a-methyloctahydroinden-1-yl]-1-ethanone demonstrates the potential utility of the method in complex synthesis.
Keywords: enynes; β-hydride elimination; cobalt; cycloisomerization; furans